In Vitro and In Vivo Antileishmanial Activity of Thioridazine - Sifontes-Rodríguez, Sergio; Mollineda-Diogo, Niurka; Monzote-Fidalgo, Lianet; Escalona-Montaño, Alma Reyna; Escario García-Trevijano, José Antonio; Aguirre-García, María Magdalena; Meneses-Marcel, Alfredo (Acta parasitologica, 2024)
Introduction Leishmaniasis is a neglected disease with high prevalence and incidence in tropical and subtropical areas. Existing drugs are limited due to cost, toxicity, declining efficacy and unavailability in endemic places. Drug repurposing has established as an efficient way for the discovery of drugs for a variety of diseases. Purpose The objective of the present work was testing the antileishmanial activity of thioridazine, an antipsychotic agent with demonstrated effect against other intracellular pathogens. Methods The cytotoxicity for mouse peritoneal macrophages as well as the activity against Leishmania amazonensis , Leishmania mexicana and Leishmania major promastigotes and intracellular amastigotes, as well as in a mouse model of cutaneous leishmaniasis, were assessed. Results Thioridazine inhibited the in vitro proliferation of promastigotes (50% inhibitory concentration—IC 50 —values in the range of 0.73 µM to 3.8 µM against L. amazonensis , L. mexicana and L. major ) and intracellular amastigotes (IC 50 values of 1.27 µM to 4.4 µM for the same species). In contrast, in mouse peritoneal macrophages, the 50% cytotoxic concentration was 24.0 ± 1.89 µM. Thioridazine inhibited the growth of cutaneous lesions and reduced the number of parasites in the infected tissue of mice. The dose of thioridazine that inhibited lesion development by 50% compared to controls was 23.3 ± 3.1 mg/kg and in terms of parasite load, it was 11.1 ± 0.97 mg/kg. Conclusions Thioridazine was effective against the promastigote and intracellular amastigote stages of three Leishmania species and in a mouse model of cutaneous leishmaniasis, supporting the potential repurposing of this drug as an antileishmanial agent.